2011
DOI: 10.1002/ijc.26412
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of large tumors expressing human papillomavirus E7 protein by therapeutic vaccination with E7 fused to the extra domain a from fibronectin

Abstract: Cervical carcinoma is one of the most common cancers in women worldwide. It is well established that chronic infection of the genital tract by various mucosatropic human papillomavirus (HPV) types causes cervical cancer. Cellular immunity to E7 protein from HPV (HPVE7) has been associated with clinical and cytologic resolution of HPV-induced lesions. Thus, we decided to test if targeting of HPVE7 to dendritic cells using a fusion protein containing the extra domain A (EDA) from fibronectin, a natural ligand fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…This immunogen, which we had previously demonstrated to be useful in the treatment of TC-1 tumors, 32 contains HPVE7 protein bound to the 91-amino acid extra domain A (EDA) from fibronectin, a TLR4 ligand which targets antigens to DC and induces its maturation, promoting the induction of T cell responses. As in B16-OVA-bearing mice, no clear differences were observed in tumor homogenates (data not shown), whereas serum IL-10 levels increased after vaccination (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This immunogen, which we had previously demonstrated to be useful in the treatment of TC-1 tumors, 32 contains HPVE7 protein bound to the 91-amino acid extra domain A (EDA) from fibronectin, a TLR4 ligand which targets antigens to DC and induces its maturation, promoting the induction of T cell responses. As in B16-OVA-bearing mice, no clear differences were observed in tumor homogenates (data not shown), whereas serum IL-10 levels increased after vaccination (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins containing the EDA from fibronectin EDA-OVA and EDA-HPV were produced as described. 32,42 Endotoxin levels in these proteins were below 0.2 EU/mg protein. OVA protein (low endotoxin) was purchased from Hyglos (321001).…”
Section: Cd8mentioning
confidence: 91%
“…In the second model, TC-1 P3 (A15) cells (5 3 10 5 cells/mouse) with a downregulated MHC class I expression (27) were injected s.c. in C57BL/6 mice (n = 6). Five days later, mice were vaccinated with 3 nmol recombinant fusion protein EDA-HPVE7 in saline (vaccine) (28). A group of vaccinated mice received also peritumoral administration of the peptide FOXP3 393-403 (a daily administration of 100 mg peptide per mouse from day 5 to day 15).…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…hepatitis C virus peptide [13] or Human Papilomavirus E7 protein [14]. We have also observed that EDA exerts its adjuvant effect more efficiently when delivered not far 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 apart but in close contact with the antigen (San Román et al, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these observations suggest that the expression of EDA in response to tissue injury, or other cellular warning signals, might induce recruitment of dendritic cells to the site of injury and trigger their subsequent maturation. Indeed, previous work demonstrates that EDA, as fusion protein, may constitute a strategy to target viral or tumoral antigens to dendritic cells in vivo [11,13,14]. Therefore, the capacity of EDA to induce dendritic cell maturation through TLR4 activation may also favor antigen uptake, expression of co-stimulatory signals, antigen presentation and the induction of anti-viral or antitumoral T cell responses [11,13].…”
Section: Introductionmentioning
confidence: 99%